2012
DOI: 10.1590/s0100-06832012000100024
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency symptoms and uptake of micronutrients by castor bean grown in nutrient solution

Abstract: José lavres Junior (2) , cleusa pereira cabral (3) , mônica lanzoni rossi (4) , thiago assis rodrigues nogueira (5) , neusa de lima nogueira (6) & eurípedes malavolta ( (1) recebido para publicação em 28 de maio de 2010 e aprovado em 11 de novembro de 2011. (2) professor Doutor do centro de energia nuclear na agricultura, Universidade de São paulo, Laboratório de nutrição mineral de plantas -cena/USp. caixa postal 96. av. centenário 303, cep 13400-970 piracicaba (Sp). e-mail: jlavres@cena.usp.br (3) bióloga do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
2
0
1
Order By: Relevance
“…In general, the Mn concentration was on average almost twice as much in leaf (268 mg•kg -1 ) than in root (141 mg•kg -1 ), while the concentration in stem (20 mg•kg -1 ) was 14 times less than in leaf. The same behavior could be observed in the study carried out by Lavres-Junior et al (2012) since the Mn was more concentrated in leaf than root and stem. The application of biosolids increased the concentration in the three organs more than the application of AS (Table 4).…”
Section: Riesgo De Contaminaciónsupporting
confidence: 83%
See 2 more Smart Citations
“…In general, the Mn concentration was on average almost twice as much in leaf (268 mg•kg -1 ) than in root (141 mg•kg -1 ), while the concentration in stem (20 mg•kg -1 ) was 14 times less than in leaf. The same behavior could be observed in the study carried out by Lavres-Junior et al (2012) since the Mn was more concentrated in leaf than root and stem. The application of biosolids increased the concentration in the three organs more than the application of AS (Table 4).…”
Section: Riesgo De Contaminaciónsupporting
confidence: 83%
“…Applying biosolids significantly increased the Zn concentration in the three organs evaluated; the higher the application rate, the greater the Zn concentration in root and stem, but not in the leaves (Table 4). Lavres-Junior et al (2012) observed that Zn was concentrated to a greater extent in root (62.3 mg•kg -1 ) and leaf (59.2 mg•kg -1 ). In the present study, the average concentration in leaf was 73 mg•kg -1 .…”
Section: Plant Nutrient Concentrationsmentioning
confidence: 91%
See 1 more Smart Citation
“…B is the second most demanded micronutrient in cowpea (Ara ujo et al, 1984;Oliveira and Dantas, 1984), and its deficiency limits crop productivity. This B deficiency may induce changes in the cell wall and cause middle lamella thickening, chloroplast deformation in castor (Ricinus communis) (Lavres J unior et al, 2012), and starch grain accumulation in cowpea (Vigna unguiculata) leaf chloroplasts (Inbaraj and Muthuchelian, 2011).…”
mentioning
confidence: 99%